Investigate The Efficacy of Utilising Arduino Materials With a Chatbot: Action Research - Koçak, Edanur; Yalçın-Çelik, Ayşe (Research Trends In Educational Sciences, 2025)
The aim of this research is to determine the effectiveness of chatbots in solving the difficulties experienced in the process of integrating microcontroller cards such as Arduino into educational environments (e.g. writing code, running Arduino kits). The preferred chatbot was ChatGPT. The research method is action research. Action research is an effective method used to solve the problems encountered in the educational process. The research was carried out with 5 female teachers who are postgraduate students in the Department of Chemistry Education at a state university. The participants had no previous training on microcontroller boards such as Arduino and no experience with chatbots. The worksheets used by the group of participants during the application process and the focus group interview were used as data collection tools. The analyses were carried out using content analysis. As a result of the analysis, it was concluded that chatbots were effective in different areas such as problem solving and code generation.